EVOO Promotes a Less Atherogenic Profile Than Sunflower Oil in Smooth Muscle Cells Through the Extracellular Vesicles Secreted by Endothelial Cells - Santiago-Fernandez, Concepción; Rodríguez-Díaz, Cristina; Ho-Plagaro, Ailec; Gutierrez-Repiso, Carolina; Oliva-Olivera, Wilfredo; Martin-Reyes, Flores; Mela, Virginia; Bautista, Rocío; Tome, Mónicas; Gómez-Maldonado, Josefa; Tinahones, Francisco J.; Garcia-Fuentes, Eduardo; et al. (Frontiers in Nutrition, 2022)
Background Little is known about the effect of extra virgin olive (EVOO) and sunflower oil (SO) on the composition of extracellular vesicles (EVs) secreted by endothelial cells and the effects of these EVs on smooth muscle cells (SMCs). These cells play an important role in the development of atherosclerosis. Methods We evaluated the effects of endothelial cells-derived EVs incubated with triglyceride-rich lipoproteins obtained after a high-fat meal with EVOO (EVOO-EVs) and SO (SO-EVs), on the transcriptomic profile of SMCs. Results We found 41 upregulated and 19 downregulated differentially expressed (DE)-miRNAs in EVOO-EVs. Afterwards, SMCs were incubated with EVOO-EVs and SO-EVs. SMCs incubated with SO-EVs showed a greater number of DE-mRNA involved in pathways related to cancer, focal adhesion, regulation of actin cytoskeleton, and MAPK, toll-like receptor, chemokine and Wnt signaling pathways than in SMCs incubated with EVOO-EVs. These DE-mRNAs were involved in biological processes related to the response to endogenous stimulus, cell motility, regulation of intracellular signal transduction and cell population proliferation. Conclusion EVOO and SO can differently modify the miRNA composition of HUVEC-derived EVs. These EVs can regulate the SMCs transcriptomic profile, with SO-EVs promoting a profile more closely linked to the development of atherosclerosis than EVOO-EVs.